2018
DOI: 10.3389/fpls.2018.00760
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics of Early Stage Plant Cell–Microbe Interaction Using Stable Isotope Labeling

Abstract: Metabolomics has been used in unraveling metabolites that play essential roles in plant–microbe (including pathogen) interactions. However, the problem of profiling a plant metabolome with potential contaminating metabolites from the coexisting microbes has been largely ignored. To address this problem, we implemented an effective stable isotope labeling approach, where the metabolome of a plant bacterial pathogen Pseudomonas syringae pv. tomato (Pst) DC3000 was labeled with heavy isotopes. The labeled bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 64 publications
0
25
0
Order By: Relevance
“…On the contrary, the approach we adopted (i.e., incorporation of isotopic labeling with untargeted metabolomics) predicted the labeling pattern of each individual metabolite species detected, giving a more comprehensive ability to track each metabolite's fate (Huang et al, 2014). Similar approaches have been used to track metabolites produced by Pseudomonas syringae during interaction with Arabidopsis epidermal cells on the leaves (Pang et al, 2018). Our result suggested that a significant number of detected molecular features (202 out of 518 in total) in Pisolithus-treated roots are highly 13 C-enriched, implying that these 13 C-labeled metabolites are putatively originated from the ECM fungus even after only 24 h of interaction, despite the low detection intensity.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, the approach we adopted (i.e., incorporation of isotopic labeling with untargeted metabolomics) predicted the labeling pattern of each individual metabolite species detected, giving a more comprehensive ability to track each metabolite's fate (Huang et al, 2014). Similar approaches have been used to track metabolites produced by Pseudomonas syringae during interaction with Arabidopsis epidermal cells on the leaves (Pang et al, 2018). Our result suggested that a significant number of detected molecular features (202 out of 518 in total) in Pisolithus-treated roots are highly 13 C-enriched, implying that these 13 C-labeled metabolites are putatively originated from the ECM fungus even after only 24 h of interaction, despite the low detection intensity.…”
Section: Discussionmentioning
confidence: 99%
“…Many integrated techniques of NMR have been applied to identify the structural units of unknown metabolites. Recently developed advanced tools for plant metabolomics are one-and two-dimensional NMR [28], isotope-labeled NMR [29], and micro-coil NMR [30]. NMR is the only tool that can detect the specific labelling of stable isotopes [3].…”
Section: Advanced Tools For Analytical Research In Plant Metabolomicsmentioning
confidence: 99%
“…The interaction between plants and microorganisms is known to triggers signaling cascade and metabolic responses. However, the main issue of analyzing changes in the plant metabolic profile during the interaction plant cell-microorganism is avoiding contamination with metabolites from the coexisting microorganism (Pang et al 2018). A very recent work addressed this issue by implementing an effective stable isotope labeling approach coupled to LC-MRM-MS measurements (Pang et al 2018).…”
Section: The Guard Cell Metabolome During Plant Cellmicroorganism Intmentioning
confidence: 99%